(untitled) (KYAMC Journal, 2020)
Background: Drug addiction is a burning problem in Bangladesh affecting a majority of population especially the youths. Multiple drug use has aggravated the overall situation affecting our personal, economical, social life and impairing health status. Objective: The objective of this study was to find out the variety of common drugs used by drug addicted young population in Dhaka City. Materials and Methods: This descriptive cross sectional study was performed during July 2016 to December 2016 at five drug addiction treatment and rehabilitation centre in Dhaka. A total of 57 habitual drug addicted young people aged 15 to 24 years were selected by purposive and convenient method of sampling. The primary data was collected by repeated visit to centers and face to face interview with addicts and their family members using a pre tested semi structured questionnaire containing both closed and open ended query. Collected data were compiled and analyzed. Results: Most 45(78.95%) of the drug addicted were male and among them 12(21.05%) belonged to age group 15-17 years. Considering occupation, majority were students 14(24.56%) followed by unemployed 12(21.05%). Thirty five (61.40%) were the lone earning member of the family. Thirty seven (75.51%) collected money for drug from family members and stealing from house followed by criminal activities 26(53.06%). Majority of the addicts (85.96%) started taking drugs after being influenced by friends. Causes of drug addiction included unemployment 12(21.05%) followed by peer pressure 9(15.79%). The commonly used drugs included-Barbiturates/Sedatives 32(56.14%), Yaba 28(49.12%), Toluene/Aica 22(38.59%). Conclusion: The dangers of drug addiction have affected all class population of our country. Preventive measures for drug smuggling and addiction are needed to be taken. More drug addiction treatment and rehabilitation centres are required to combat present situation. KYAMC Journal Vol. 11, No.-2, July 2020, Page 73-76